ChemInform Abstract: A Cinchona Alkaloid Catalyzed Enantioselective Sulfa‐Michael/Aldol Cascade Reaction of Isoindigos: Construction of Chiral Bispirooxindole Tetrahydrothiophenes with Vicinal Quaternary Spirocenters. Issue 39 (September 2015) - Gui, Yong‐Yuan; Yang, Jian; Qi, Liang‐Wen; Wang, Xiao; Tian, Fang; Li, Xiao‐Nian; Peng, Lin; Wang, Li‐Xin
Abstract The first protocol for the asymmetric preparation of the highly congested title compounds by an organocatalytic cascade reaction is presented.